Given
The equations are given
a) 4t^2 - 5t = 0
d) (y + 6)(y - 6) = - (y + 6)^2
h) (u - 4)(u + 4) = (u + 2)(u - 2).
Step-by-step explanation
a. 4t^2 - 5t = 0
![\begin{gathered} t(4t-5)=0 \\ t=0,4t-5=0 \\ t=0,t=(5)/(4)=1.25 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/3bmc1gtij7y2ivaa3qv54lpaofum2gfnht.png)
d. (y + 6)(y - 6) = - (y + 6)^2
![\begin{gathered} y^2-6y+6y-36=-(y^2+36+12y) \\ y^2-36=-y^2-36-12y \\ y^2+y^2+36-36+12y=0 \\ 2y^2+12y=0 \\ 2y(y+6)=0 \\ y=0,y=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/a3xmd9cp9di4g85i0vq4a2f77mt3sp5u66.png)
h. (u - 4)(u + 4) = (u + 2)(u - 2).
![\begin{gathered} u^2+4u-4u-16=u^2-2u+2u-4 \\ u^2-16=u^2-4 \\ u^2-16-u^2+4=0 \\ -12\\e0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/eqvgzmmgpt9ghxb9vl09lnfh6bs2javlkb.png)
Answer
Hence the solution to the equations are
![\begin{gathered} a.t=0,1.25 \\ d.\text{ y=0,-6} \\ h.\text{ no solution} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/aqvqbey6oy9zstw9jjrlrqyo8crwr5nm30.png)